Supply Chain Project Studies - One, ITM-OM Team; Sorooshian, Shahryar; Kamar, Ahmad Nazif Bin Noor (Journal of Management and Science, 2013)
This article is a mini review paper to explore recent studies in supply chain management for a class activity in Operations management tutorial under University Malaysia Pahang Undergraduate Programs. In this paper a team of students as their tutorial work studied researches to find what the role of manager of chain of suppliersis.